Penerapan Decission Support System Dalam Pemilihan Karyawan Berprestasi Menggunakan Metode Promethee - Jarot Dian Susatyono; Haryo Kusumo; Rusito Rusito; Febryantahanuji (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
The number of employees who are not enthusiastic in discipline at work has a bad impact on the production division, which is currently still busy with orders for wood processing. This is because the company still applies casual daily wages for contract workers. In addition, there are still many employees who are often absent every day for various reasons. To support the decision of the HRD head, a decision support system is needed to select outstanding employees in the company. In this decision support system will use the promethee method with attributes that have been adjusted to the company's problems